2021
DOI: 10.1200/jco.20.02272
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Elacestrant (RAD1901), a Novel Selective Estrogen Receptor Degrader, in ER-Positive, HER2-Negative Advanced Breast Cancer

Abstract: PURPOSE This phase I study (RAD1901-005; NCT02338349) evaluated elacestrant, an investigational oral selective estrogen receptor degrader (SERD), in heavily pretreated women with estrogen receptor–positive, human epidermal growth factor receptor 2–negative metastatic breast cancer, including those with estrogen receptor gene alpha ( ESR1) mutation. The primary objective was to determine the maximum tolerated dose and/or recommended phase II dose (RP2D). METHODS The study consisted of a 3 + 3 design (elacestran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 25 publications
(44 reference statements)
0
65
0
2
Order By: Relevance
“…In addition, some of these SERDs are effective preclinically against ESR1-MUT in cell lines and in PDX models that have complete fulvestrant resistance, through unknown mechanisms [ 38 , 39 , 53 ]. Elacestrant (RAD1901) has been effective against cells and PDX models with fulvestrant and CDK4/6i resistance [ 51 ], and Phase 1 data show efficacy in ESR1-MUT patients and patients pretreated with fulvestrant and CDK4/6i [ 54 ]. Elacestrant is in a Phase 3 trial for patients after progression on ET and CDK4/6i (EMERALD: NCT03778931).…”
Section: Esr1 Mutations and Selective Estrogen Receptor Degradersmentioning
confidence: 99%
“…In addition, some of these SERDs are effective preclinically against ESR1-MUT in cell lines and in PDX models that have complete fulvestrant resistance, through unknown mechanisms [ 38 , 39 , 53 ]. Elacestrant (RAD1901) has been effective against cells and PDX models with fulvestrant and CDK4/6i resistance [ 51 ], and Phase 1 data show efficacy in ESR1-MUT patients and patients pretreated with fulvestrant and CDK4/6i [ 54 ]. Elacestrant is in a Phase 3 trial for patients after progression on ET and CDK4/6i (EMERALD: NCT03778931).…”
Section: Esr1 Mutations and Selective Estrogen Receptor Degradersmentioning
confidence: 99%
“…The clinical benefit was associated with a decline in ESR1 mutant allele fraction. This study concluded that elacestrant 400 mg orally once daily has an acceptable safety profile and demonstrated single-agent activity with confirmed partial responses in heavily pretreated patients with ER+ MBC, in patients with ESR1 mutation as well as those with prior CDK4/6i and prior SERD [73] (Table 2).…”
Section: Rad1901 (Elacestrant)mentioning
confidence: 84%
“…As mentioned above, fulvestrant is the only approved SERD for the therapy of postmenopausal aBC patients to date. However, since there is a lack of oral bioavailability of fulvestrant, therefore requiring intramuscular injection of it [ 83 , 84 ], other novel SERDs with the potential of oral bioavailability are being investigated [ 85 , 86 , 87 , 88 , 89 ] ( Table 2 ). A first-in-human study on the SERD AZD9496, for instance, showed an acceptable safety profile and a prolongation of disease stabilization in women with hormone-receptor-positive aBC [ 90 ], but its preoperative influence on estrogen receptor expression was not superior to fulvestrant within a recent window of an opportunity trial in eBC [ 91 ].…”
Section: Modern Approaches In Advanced Breast Cancermentioning
confidence: 99%